Determinación de parámetros tecnológicos óptimos para la elaboración y conservación de pulpa de cocona (solanum sessiliflorum dumal) concentrada con la aplicación de método de factores combinados - Villegas Valle, Javier Alejandro (2015)
The Cocona is a native fruit with enough economic potential in the Peruvian Amazon. Due to the large production of cocona in the San Martin region and the increase in daily demand for this fruit was the need to confer added value given the importance acquired as agro raw materials likely to be programmed and channeled for industrialization in a range of products such as refined pulp, juices and nectars, fruit jellies, marmalades, syrups, ates, compotas, among other products of economic importance and sought by the consumar. The cocona has a high nutritional value, rich in iron and ascorbic acid; addition of calcium, phosphorus and trace amounts of carotene, and niacin. This fruit has a low caloric intake and significant content of dietary fiber. The research work presents a brief description of the mechanism of action of sorne microbial stress factors, which when applied in combination, result in the call preservation by combinad methods and technology obstacles. Microbial stability and safety of many foods are based on the combination of factors or obstacles. The obstacle concept explains the fact that the complex interactions among microbial factors such as stress aw, pH, temperature and addition of antimicrobials are significant to the microbial stability of food. Taking the example of applying this technology to cocona, which by its acidic nature, allows relatively simple and inexpensive way, this combination of factors to keep them. The use of 0.1 % ascorbic acid, 0.04% sodium erythorbate, and 0.05% potassium sorbate; were appropriate, with which the stability of the product was achieved; coupled to a heat treatment of 95 º C for 5 minutes as the right to retain pulp cocona, confirmad by microbiological results after 30 days of storage assertion; in which microbial growth to a minimum is below the maximum permissible observed.